SPPEK/TPA composite membrane as a separator of vanadium redox flow battery - Wang, Nanfang; Yu, Jingang; Zhou, Zhi; Fang, Dong; Liu, Suqin; Liu, Younian (Journal of membrane science, 2013)
To improve the performance of a low cost sulfonated poly(phthalazinone ether ketone) (SPPEK) membrane in vanadium redox flow battery (VRFB), composite membranes composed of SPPEK and tungstophosphoric acid (TPA) with 8–25wt% concentration were prepared by solution casting. The results of scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDS), and X-ray diffraction (XRD) of the SPPEK/TPA composite membrane revealed that TPA had excellent compatibility with SPPEK in the bulk of the membrane. The effect of the TPA concentration on the primary properties, permeability of vanadium ions and ionic selectivity, and chemical stability of the composite membrane was investigated. The single cell tests showed that the VRFB employing the SPPEK–TPA-17 membrane with 17wt% TPA exhibited a higher coulombic efficiency (98.75% vs. 92.81%) and energy efficiency (74.58% vs. 73.83%) than those of the Nafion system. Cycling and chemical stability tests indicated that the SPPEK/TPA composite membrane had high stability in the VRFB system. ► A SPPEK/TPA composite membrane by the solution casting method was investigated in VRFB application. ► The introduction of TPA (8–25wt%) can improve the proton conductivity. ► VRFB with the composite membrane exhibited superior performance compared with Nafion membrane.